A sketch of Antonio Candido's poetics - Prado, Márcio Roberto do (ITINERÁRIOS – Revue de Littérature, 2010)
This paper aims at presenting an introduction to Antonio Candido’s poetics, in which it concerns the discussion about the limits of literary criticism and literature.